2010
DOI: 10.1055/s-0030-1249093
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis of a Skin Autograft After Short-Term Treatment with Sunitinib in a 14-Year-Old Girl with Metastatic Alveolar Soft Part Sarcoma of the Thigh

Abstract: A 14-year-old girl was diagnosed with alveolar soft part sarcoma (ASPS) of the thigh and lung metastases. She underwent tumor resection and pulmonary metastasectomy followed by hyperfractionated local radiotherapy (44.8 Gy). A mesh graft transplant was used to cover the postoperative skin defect on the thigh. Since ASPS do not respond to conventional chemotherapy antiangiogenic treatment with peginterferon alfa-2b and thalidomide was started. Immunohistochemical analysis of tumor tissue showed expression of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The maximum tolerated dose for patients without cardiac risk factors is 15 mg/m 2 for four consecutive weeks and rest for 2 weeks (54). Studies have shown that sunitinib has a good effect on children with advanced ASPS and can improve their quality of life (51), but it should be used cautiously in patients with severe skin injury (34). ( 5) Immune checkpoint inhibitors: immune checkpoint inhibitors can activate the effect of human autoimmune response against tumors and have a more lasting effect.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum tolerated dose for patients without cardiac risk factors is 15 mg/m 2 for four consecutive weeks and rest for 2 weeks (54). Studies have shown that sunitinib has a good effect on children with advanced ASPS and can improve their quality of life (51), but it should be used cautiously in patients with severe skin injury (34). ( 5) Immune checkpoint inhibitors: immune checkpoint inhibitors can activate the effect of human autoimmune response against tumors and have a more lasting effect.…”
Section: Discussionmentioning
confidence: 99%
“…For multiple brain metastases, some researchers administered palliative whole-brain radiotherapy with 30 Gy in 10 fractions, but prognosis was poor because of the widespread metastases in advanced cases [25] . For single lung metastasis of ASPS, hyperfractionated local radiotherapy could be considered with total dose of 44.8 Gy [26] …”
Section: Therapeutic Methodsmentioning
confidence: 99%
“…[25] For single lung metastasis of ASPS, hyperfractionated local radiotherapy could be considered with total dose of 44.8 Gy. [26] Carbon-ion radiotherapy also showed satisfactory effects. There was a case report that a 9-year old girl who was diagnosed as ASPS with the tumor locating in the upper third of the vagina, received carbon-ion radiotherapy with 67.2 Gy in 16 fractions at the part of the tumor adhered to the posterior pubis which was residual after resection, the tumor decreased gradually without recurrence for 20 months, the patient had not any adverse effects.…”
Section: Radiotherapymentioning
confidence: 96%
“…For the lung metastasis of ASPS, whole-lung irradiation is generally not performed as for other subtypes of STS except Ewing sarcoma. Strategies combining metastasectomy and RT may be used; a case report indicated the use of hyperfractioned local RT with a total dose of 44.8 Gy (2 × 1.6 Gy daily) following pulmonary metastasectomy ( 59 ).…”
Section: The Management Of Advanced/metastatic Aspsmentioning
confidence: 99%